Seni sebagai Media Dakwah Pembinaan Akhlak - Raga Bagus Satriya (Jurnal Komunikasi, 2019)
The As-Salim art boarding school is known as the "art" hut, because the students there have various abilities and skills. The students were fostered by KH. Miftachul Munir majority are orphans, who are usually synonymous with "naughty". From the mischief, KH. Miftachul Munir tried to draw their attention to the field of art with Islamic nuances. This research is a qualitative research. Data collected by observation, interviews, and documentation. With qualitative descriptive data analysis, and phenomenology approach. The results of the study show that 1) KH. Miftachul Munir in carrying out his indictment activities used media preaching arts. The process of his da'wah in fostering santri morality began with his efforts to establish As-Salim Islamic boarding school. 2) The advantages of the art media preaching are still very rarely applied by the public in santri moral formation. While the drawback is that not all da'i are able to implement it. Keywords: Art, Da'wah Media, Moral Development